ODIN: Star Formation Histories Reveal Formative Starbursts Experienced by Lyα-emitting Galaxies at Cosmic Noon - Nicole M. Firestone; Eric Gawiser; Kartheik G. Iyer; Kyoung-Soo Lee; Vandana Ramakrishnan; Francisco Valdes; Changbom Park; Yujin Yang; Anahita Alavi; Robin Ciardullo; Norman Grogin; Caryl Gronwall; et al. (The Astrophysical Journal Letters)
In this work, we test the frequent assumption that Ly α -emitting galaxies (LAEs) are experiencing their first major burst of star formation at the time of observation. To this end, we identify 74 LAEs from the ODIN Survey with rest-UV-through-NIR photometry from UVCANDELS. For each LAE, we perform nonparametric star formation history (SFH) reconstruction using the Dense Basis Gaussian-process-based method of spectral energy distribution fitting. We find that a strong majority (67%) of our LAE SFHs align with the frequently assumed archetype of a first major star formation burst, with at most modest star formation rates (SFRs) in the past. However, the rest of our LAE SFHs have significant amounts of star formation in the past, with 28% exhibiting earlier bursts of star formation, with the ongoing burst having the highest SFR (dominant bursts) and the final 5% having experienced their highest SFR in the past (nondominant bursts). Combining the SFHs indicating first and dominant bursts, ∼95% of LAEs are experiencing their largest burst yet: a formative burst. We also find that the fraction of total stellar mass created in the last 200 Myr is ∼1.3 times higher in LAEs than in mass-matched Lyman break galaxy (LBG) samples, and that a majority of LBGs are experiencing dominant bursts, reaffirming that LAEs differ from other star-forming galaxies. Overall, our results suggest that multiple evolutionary paths can produce galaxies with strong observed Ly α emission.